Perlindungan Hukum Bagi Pembeli Tanah Beritikad Baik Atas Sertifikat Ganda - Ridwan, M; Vitrianingsih, Yeni (PATTIMURA Law Study Review, 2025)
Multiple land titles are a serious problem in Indonesia's land system as they cause great harm, especially to good faith buyers. Legal uncertainty and a weak land administration system mean that buyers are often caught up in disputes. This condition shows the need for clear and effective legal protection in land sale and purchase transactions. The purpose of this research is to find out the relationship between laws and regulations, namely Law Number 5 of 1960 concerning Agrarian Principles and Government Regulation Number 24 of 1997 concerning Land Registration in terms of providing legal protection to buyers who suffer losses due to double certification. This research uses a normative legal method with a qualitative approach, by conducting a literature review and analysis of a number of court cases. The results show that legal protection for good faith land buyers has been normatively guaranteed through the Basic Agrarian Law and Government Regulation on Land Registration. However, in practice, buyers remain vulnerable to losses due to multiple certificates due to weak administrative verification, overlapping measurements and procedural irregularities by land agencies. Disputes often arise even when buyers have complied with all legal procedures. This research emphasizes the importance of improving the land administration system, strengthening the role of the National Land Agency, and consistency in court decisions to realize fair and effective legal protection for buyers.